2020
DOI: 10.1108/idd-12-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mobile learning needs amongst performing arts students

Abstract: Purpose This paper aims to study the information needs and online information-seeking behaviors on mobile platforms of performing arts students at a college level. Design/methodology/approach Survey instruments were used to collect data from performing arts students at the Hong Kong Academy of Performing Arts (HKAPA), a metropolitan’s major performing arts tertiary institution. Data collected were analyzed through descriptive statistics and other statistical methods, and the music-related students were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Mobile technology involving wireless networks, smartphones and tablets is inherent in the life of the younger generation nowadays, regardless of their academic discipline. Our findings are consistent with the results of other studies in that many students have indicated a tendency to use their smartphones to engage in various leisure, recreational and relaxation activities, such as watching videos and listening to music (Fan et al, 2020; Ko et al, 2015; Wai et al, 2018). The medical student respondents in this study are no exception; the majority are digital natives and have been using mobile technology daily for a variety of social and entertainment purposes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mobile technology involving wireless networks, smartphones and tablets is inherent in the life of the younger generation nowadays, regardless of their academic discipline. Our findings are consistent with the results of other studies in that many students have indicated a tendency to use their smartphones to engage in various leisure, recreational and relaxation activities, such as watching videos and listening to music (Fan et al, 2020; Ko et al, 2015; Wai et al, 2018). The medical student respondents in this study are no exception; the majority are digital natives and have been using mobile technology daily for a variety of social and entertainment purposes.…”
Section: Discussionsupporting
confidence: 92%
“…The findings from this study extend and reinforce earlier studies (Dukic et al, 2015; Fan et al, 2020; Ko et al, 2015; Lau et al, 2020) in that these medical student respondents commonly used mobile devices for looking up quick facts, as well as for a variety of social networking and recreational purposes. For example, a majority of the respondents indicated that they used mobile devices for the following purposes: ‘instant messaging’; ‘accessing search engines’; ‘checking or sending emails’; ‘social networking and sharing’; and ‘getting directions’ (see Table 5).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These measures may not be necessary long-term, but as we learn how to adapt to what some call the "new normal" it is important to explore all of our options. Noted by Fan et al (2020), the majority of students and educators own mobile devices which are comparable to desktop computers; the capacity to teach and learn from a device is present. Social media applications are also more likely to be used by students overall than any other non-academic applications (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Noted by Fan et al (2020), the majority of students and educators own mobile devices which are comparable to desktop computers; the capacity to teach and learn from a device is present. Social media applications are also more likely to be used by students overall than any other non-academic applications (Fan et al, 2020). Additionally, the majority of college-age students take in their news through social media (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%